Development of a Field Laboratory to Social Science Education Pre-Service Teacher - Abdul Bashith; Saiful Amin; Ramadhani Lausi Mkumbachi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
This study aims 1) to describe the physical, social, economic, and cultural potential of the Social Science Education field laboratory object on the slopes of Mount Tengger and 2) to produce a product in the form of a manual for the Social Science Education field laboratory. The Dick and Carey model was used in this development with simplified stages. Qualitative data are in the form of 1) a description of the object of research and (2) suggestions for product improvement from the validator of learning and design experts. Quantitative data are in the form of response scores from expert validators and students during limited trials. The instruments in this study were observation sheets, interview guidelines, documentation, and questionnaires. The data analysis used in this study is a descriptive analysis to examine the relevance of various subjects in the Social Science Education Department with the objects that are scattered in the study area. Furthermore, descriptive statistical analysis is used to process the questionnaire data with a Likert scale of 1 (very poor) to 4 (very good). The results showed that first, the physical, social, economic, and cultural potential in the research object supported the feasibility of developing a social science education field laboratory. Second, the manual for the Social Science Education field laboratory is suitable for use in outdoor social studies learning with a feasibility value of 87.25 (very feasible).